Pengendalian Biaya Prouksi pada PT. Industri Jamu dan Farmasi Sido Muncul TBK. - Fadlia Salsadila; Chantika Jasmine; Dede Ibrahim; Hidayat Nur Rahman; Karolina Cahyani Demong (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this study is to understand the production cost budget prepared by PT Jamu and Farmasi Sido Muncul Tbk. The study also has the objective to assess the application of flexible budget as a means to control production cost in Semarang City. The method applied in this study is qualitative analysis, which includes comparison between fixed budget and flexible budget, as well as calculation between budget and actualization of production cost. Based on the analysis conducted, it was found that when designing the budget for production cost at PT Jamu and Farmasi Sido Muncul Tbk, the static budget formed based on activity level reached Rp 18,706,958. However, the realization achieved was only Rp 10,761,351. This situation is considered unsatisfactory because the realization did not reach the target, which was caused by several factors such as technical delays, equipment breakdowns, and difficulties in obtaining basic materials, all of which had an impact on the overall total production cost.